VISUAL MYTHOLOGY REYOG PONOROGO IN ARTIFICIAL INTELEGENT - Nugroho, Oki Cahyo; Tricana, Deny Wahyu; Pinaryo, Pinaryo; Lestarini, Niken (Jurnal Ilmiah Dinamika Sosial, 2024)
Reyog Ponorogo is an artwork with a rich history and folklore, as well as a particular visual narrative that is worth studying through the lens of visual data studies. Reyog performers offer significant meanings via the visuals of their performance as well as the ideology of Ponoragan Javanese culture. The purpose of this project is to convert oral myths into visual signals in Reyog performances using visual data. Using W.J.T. Mitchell's "Picture Theory" method, this research investigates the complicated interplay between pictures and text, introducing the idea of "imagetext" as one manifestation of this interaction. The method used is a prompt-based descriptive approach in which keywords are entered to instruct the artificial intelligence (AI) system to translate the command into a visual form, as well as a re-representation technique based on "picture words" in an effort to create images with narratives rooted in Reyog Ponorogo mythology. This study included two AI systems: Leonardo AI and Midjourney. The study found that the AI system is not entirely capable of understanding local regional languages, leading to plot discrepancies between pictures in the same story series. Nonetheless, this technique adds a new dimension to visual communication technology, particularly in the delivery of visual messages using AI.